A Savings Application Design Concept Model in Website-Based Cooperative Units - Rafli Husain Kurniawan; Irfan Santiko; Gustin Setyaningsih (Journal of Multimedia Trend and Technology, 2023)
Data Processing of data for cooperative operational activities such as the process of savings, loans, and installments that still use manual calculations. Incoming data is still recorded so it takes a long time for the next process which is less efficient and sometimes errors occur in data entry. To overcome this, a system is needed to expedite and speed up these activities so that in the data entry process there are no errors. Extreme Programming modeling is the method that will be used by researchers to create the system, while for the data collection process, interviews, observations, and documentation are used. The tools used are PHP programming language, MySQL database, and system development using DFD (Data Flow Diagram). The expected result is a savings and loan cooperative information system and the computational process for the cooperative system can be implemented.